Pengembangan Konseling Kelompok dengan Teknik Token Ekonomi untuk Meningkatkan Perilaku Student Engagement: Studi Penelitian Pengembangan Strategi Konseling Kelompok Pada Siswa SMP Negeri 8 Kota Cilegon Tahun Ajaran 2021/2022 - Mega Trisnawati Dewi; Raudah Zaimah Dalimunthe; Putri Dian Dia Conia (Ma'soem University, 2022)
This study aims to develop guidebook for implementing group counseling using the token economy approach in order to improve student engagement behavior for junior high school. The type of research used is research and development with research and development (R & D) Borg & Gall methods simplified by the Puslitjaknov Team (2008) which consists of conducting product analysis to be developed, developing initial products, expert validation and revision, trial small-scale field trials and revisions, large-scale field trials and final products. The sampling technique used was non-probability sampling by using purposive sampling. The number of samples that will be involved in this study are 20 students. This research is about product development in the form of a guidebook contains information about group counseling using the token economy approach in order to improve student engagement behavior. To evaluate the product to be made, the researcher uses an evaluation model of alpha test and beta test. By asking material and media experts to assess the feasibility of the product as a way to evaluate, this is called an alpha test. The beta test is a form of product feasibility test based on the prospective user's assessment of the product being developed. After the product was tested for feasibility by material and media experts, then after being tested by students, whether the product developed was feasible or not, to get the results the researcher analyzed the data that had been obtained using the eligibility criteria according to Arikunto (2009). In the product feasibility test, it was found that the results of the material expert test were 75,72%, the media expert test results were 74,29% and the user response test results were 78,58%. So from the results of the feasibility test and the respondent's trial, it was found that the product that the researcher developed in the form of guidebook was considered “feasible”.